Obstacles to Musabaqah Qiraatul Kutub for Penghulu at the Regional Office of the Indonesian Ministry of Religious Affairs - Wahib, Moh.; Amri, Amri; Islamy, Athoillah (Alhadharah: Jurnal Ilmu Dakwah, 2023)
In 2018, the Ministry of Religious Affairs of Papua Province initiated the Musabaqah Qiraatul Kutub (MQK) program for Penghulu, yet its effectiveness encountered impediments attributed to various factors. This qualitative study employed data mining techniques such as interviews, observation, and documentation, supplemented by relevant scientific literature as secondary sources. The theoretical framework utilized for analysis was Soerjono Soekanto's effectiveness theory, and data analysis unfolded through sequential stages of reduction, presentation, and verification. The findings delineate two primary inhibiting factors: a prevalent deficiency in reading and understanding the Yellow Book among participating Penghulu and constraints in budget allocation for the activities. This underscores a sociological construct, elucidating obstacles to the effectiveness of the Musabaqah Qiraatul Kutub (MQK) program. The theoretical implications underscore the imperative of enhancing human resources, facilities, and budgetary allocations to augment Penghulu competence in comprehending and interpreting the Yellow Book. It is pertinent to acknowledge the study's limitations, given the absence of an exploration into the Ministry of Religious Affairs of Papua Province's post-program strategy concerning Penghulu lacking proficiency in reading and understanding the Yellow Book.